KADIS S3 SEGER (Membudayakan Disiplin dan Sopan Santun Dengan Sehat dan Gembira) - Rejo Rejo (eductum: Jurnal Literasi Pendidikan, 2023)
Since August 2021, SMPN 3 Mojokerto initiated limited face-to-face learning, which subsequently evolved into full-fledged in-person education by January 2022, implementing health protocols in response to the COVID-19 pandemic. However, the pandemic's impact became evident in the declining character of students, notably in their discipline and courtesy. To address this issue, the school introduced an initiative known as "KADIS S3 SEGER," where public service is provided to students with the goal of enhancing their discipline and courtesy in a healthy and joyful manner. Each day before entering the school, during a specific time frame, teachers and administrative staff warmly greet students with smiles, greetings, and salutations while also conducting body temperature checks. Students traverse three distinct lanes, and this activity is executed effectively and efficiently. The "KADIS S3 SEGER" initiative successfully improved student discipline and courtesy, as evidenced by attendance data collected via fingerprint scanning, showing a reduction in student tardiness from 6.1% to 1.1%, and an increase in students' courtesy towards teachers from 84% to 94%. Furthermore, the culture of smiling, greetings, salutations, and courtesy is being increasingly ingrained within the school, providing an effective framework for in-person learning amidst the ongoing COVID-19 pandemic.